Unraveling one of the ‘Big Five’: update of the taxonomy of Triphoridae (Gastropoda, Triphoroidea) from Brazil - Fernandes, Maurício Romulo; Pimenta, Alexandre Dias (European Journal of Taxonomy, 2020)
The present study aims to fulfill the gap of taxonomic knowledge on Triphoridae from Brazil. We describe five new species (Isotriphora uncia sp. nov., Isotriphora leo sp. nov., Monophorus verecundus sp. nov., Sagenotriphora albocaput sp. nov., Similiphora lucida sp. nov.), report five species previously known only from the Caribbean and related areas (Cheirodonta dupliniana (Olsson, 1916), Eutriphora auffenbergi Rolán & Lee, 2008, Isotriphora tricingulata Rolán & Fernández-Garcés, 2015, Marshallora ostenta Rolán & Fernández-Garcés, 2008, Monophorus caracca (Dall, 1927) comb. nov.) and describe six morphotypes at the generic level (Isotriphora sp. 1, Marshallora sp. 1, Nanaphora sp. 1, Sagenotriphora sp. 1, Sagenotriphora sp. 2, Similiphora sp. 1). Remarks are made to some species previously recorded from Brazil, including the invalidation of records, problems of generic allocation and geographical range extensions. Maps of the geographical distribution are provided for the 65 currently recognized species of Triphoridae from Brazil. Of these, 31 species are endemic to Brazil and 58 inhabit the continental shelf vs only seven from the continental slope. A distinct geographical zone occurs in southeastern Brazil. A few species occur exclusively near the mouth of the Amazon River, whereas others inhabit a local biogenic reef, possibly serving as a biogeographical corridor that connects western Atlantic populations. Species of Isotriphora from Brazil are particularly common around oceanic islands, probably due to adopting intracapsular metamorphosis, which may have evolved in more than one evolutionary event.